Francisella Recognition by Inflammasomes: Differences between Mice and Men - Gavrilin, Mikhail A.; Wewers, Mark D. (Frontiers in Microbiology, 2011)
Pathogen recognition by intracellular sensors involves the assembly of a caspase-1 activation machine termed the inflammasome. Intracellular pathogens like Francisella that gain access to the cytosolic detection systems are useful tools to uncover the details of caspase-1 activation events. This review overviews Francisella function in the mononuclear phagocyte with particular attention to inflammasome versus pyroptosome roles and outlines differences between mouse and human caspase-1 activation pathways. Specific attention is placed on functional differences between human and murine pyrin as an intracellular recognition molecule for Francisella.